1) 4^(1-2x)=1/16 2) 2^(x+3) +3*2^(x+1) 3) 6*3^(2x)-3^x-5=0 4) 3^(2x+5)- 2^(2x+7)+3^(2x+4)-2^(2x+4)=0 5)2^(2x)=91^x 6)5^x=-x+6

1) 4^(1-2x)=1/16 2) 2^(x+3) +3*2^(x+1) 3) 6*3^(2x)-3^x-5=0 4) 3^(2x+5)- 2^(2x+7)+3^(2x+4)-2^(2x+4)=0 5)2^(2x)=91^x 6)5^x=-x+6
Гость
Ответ(ы) на вопрос:
Гость
1 4^(1-2x)=4^-2 1-2x=-2 2x=3 x=1,5 2 2^(x+3) +3*2^(x+1)=2^(x+1)*(4+3)=7*2^(x+1) 3 6*3^(2x)-3^x-5=0 3^x=a 6a²-a/243=0 1458a²-a=0 a(1458a-1)=0 a=0⇒3^x=0 нет решения а=1/1458⇒3^x=1/1458⇒x=log(3)1458=6+log(3)2 4 3^(2x+5)- 2^(2x+7)+3^(2x+4)-2^(2x+4)=0 3^(2x+4)*(3+1)=2^(2x+4)*(8+1) (3/2)^(2x+4)=9/4 2x+4=2 2x=-2 x=-1 5 2^(2x)=91^x 2^x=a a²-91a=0 a(a-91)=0 a=0⇒2^x=0 нет решения a=91⇒2^x=91⇒x=log(2)91 6)5^x=-x+6 y=5^x x  -1  0  1 y 0,2 1   5 y=-x+6 x    1    6 y    5    0 x=1
Не нашли ответ?
Ответить на вопрос
Похожие вопросы